Rationalizing the diverse reactivity of [1.1.1]propellane through sigma-pi-delocalization - Sterling, AJ; Dürr, A; Smith, R; Anderson, EA; Duarte, F (Royal Society of Chemistry, 2020)
[1.1.1]Propellane is the ubiquitous precursor to bicyclo[1.1.1]pentanes (BCPs), motifs of high value in pharmaceutical and materials research. The classical Lewis representation of this molecule places an inter-bridgehead C–C bond along its central axis; ‘strain relief’-driven cleavage of this bond is commonly thought to enable reactions with nucleophiles, radicals and electrophiles. We propose that this broad reactivity profile instead derives from sigma-pi-delocalization of electron density in [1.1.1]propellane. Using ab initio and DFT calculations, we show that its reactions with anions and radicals are facilitated by increased delocalization of electron density over the propellane cage during addition, while reactions with cations involve charge transfer that relieves repulsion inside the cage. These results provide a unified framework to rationalize experimental observations of propellane reactivity, opening up opportunities for the exploration of new chemistry of [1.1.1]propellane and related strained systems that are useful building blocks in organic synthesis.